PENGARUH INFORMASI KEUANGAN DAN NON KEUANGAN TERHADAP INITIAL RETURN PADA PERUSAHAAN YANG MELAKUKAN PENAWARAN UMUM SAHAM PERDANA DI BURSA EFEK INDONESIA PERIODE 2014-2016 - Nadia, Rizka; Daud, Rulfah M (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
The purpose of this study is to examine the effect of financial information (Earning Per Share (EPS), Debt To Equity Ratio (DER) and Return On Asset (ROA)) and non-financial information (Reputation Underwriter and Reputation Auditor) to initial returns on companies that do Initial public offering in Indonesia Stock Exchange period 2014-2016. The type of research used is verification research with purposive sampling method. The target population of this study is all companies that conduct initial public offering (IPO) and subsequently listed its shares (lisiting) on BEI since January 1, 2014 s.d. 31 December 2016. After the selection there are 56 research target populations. The data used in this research is secondary data. Secondary data needed in this study can be grouped into two types of data that is quantitative and qualitative data obtained from the prospectus of the company that became the sample of this study. Hypothesis testing is used by performing multiple linear analysis.The results of this study indicate that Earning Per Share, Debt to Equity Ratio, Return on Asset, Underwriter Reputation, and Reputation Auditor jointly affect the Initial Return on companies that conduct initial public offering in Indonesia Stock Exchange period 2014 s.d. 2016. Earning Per Share partially effect on Initial Return on companies that conduct initial public offering in BEI period 2014 s.d. 2016. Debt to Equity Ratio partially has no effect on Initial Return on companies that conduct initial public offering in BEI period 2014 s.d. 2016. Return on Asset partially has no effect on Initial Return on companies that conduct initial public offering in IDX period 2014 s.d. 2016. Reputation Underwriter partially effect on Initial Return on the company offering initial stock in BEI period 2014 s.d. 2016. Reputation Auditors partially influence on Initial Return on the company performing shares in the stock period in 2014 s.d. 2016